On African music : techniques, influences, scholarship - Agawu, V. Kofi 4 0 (Victor Kofi),16; 5 (New York, NY : Oxford University Press, 2023)
Composed over a decade and a half and originally delivered to audiences in Europe, Africa and the US, these lectures celebrate African musical creativity by illuminating selected compositional techniques, key influences, and dominant scholarly themes. Chapters on minimalism, iconicity, tonality as a colonizing force, and African pianism are supplemented by a critique of ethnotheory, a capsule history of African rhythm studies. and an invitation to music theorists to consider whether greater encounter with African music might not enhance the work that they do. Framed as an exercise in postcolonial criticism, the work refers to a large body of recorded music from various parts of Africa, provides close readings of a handful of compositions to supplement the more general appreciative commentary, and engages recurring and controversial talking points in contemporary discourses on African music. Written in clear and accessible prose, these self-standing essays are designed to enhance admiration for the animating structures of African music--
Introduction -- The minimalist impulse -- Iconicity in musical thought and expression -- Tonality as a colonizing force -- African pianism and the challenge of art music -- Rethinking music theory, with African aid -- Against ethno-theory -- African rhythm studies : A sketch and a critique -- Epilogue.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; History and criticism.;Social aspects;African influences. -- Music;Music;Music -- Africa;Africa. -- 20; 20; 2